Caulerpin: Biosynthetic Significance and Cytotoxic Activity Against Artemia salina Leach - Dini, Iwan (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Caulerpin (1) is one of the bisindole alkaloid compounds isolated from the many macroalga species of the Halimeda and Caulerpa genera. The biosynthetic significance of 1 is suggested by the biotransformation of indole-3-acetic acid to indole-3-carboxaldehyde via tryptophan from the shikimate pathway. This compound has many biological activities reported and this time, the 1 were evaluated for their cytotoxicity in the brine shrimp assay against A. salina Leach. in vitro and showed moderate activity with IC50 value 81.28 µg/mL.